Tennis skills & drills - Rive, Joey; Williams, Scott C. (Human Kinetics, 2012)
Over 110 proven drills in "Tennis Skills & Drills "demonstrate appropriate technique with descriptions for players to master a skill and then use that targeted skill during competition. From singles and doubles coverage to movement and tactical drills, the comprehensive coverage and full-color photos will lead you to more victories on the court